2021
DOI: 10.1186/s40463-021-00497-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of miRNA expressions among benign, premalignant and malignant lesions of the larynx: Could they be transformation biomarkers?

Abstract: Background The malignancy potential of the laryngeal lesions are one of the major concerns of the surgeons about choosing the treatment options, forming surgical margins, deciding the follow-up periods. Finding a biomarker to overcome these concerns are ongoing challenges and recently microRNAs (miRNAs) are attributed as possible candidates since they can regulate gene expressions in the human genome. The objective of our study was to investigate their capability as a transformation biomarker f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Of those, 166 were excluded for describing HNSCC cases without focus on the larynx ( n = 28), for being exclusively in vitro studies ( n = 39), for having a number of patients less than 10 or for using patient data from public databases ( n = 50), for not quantifying miRNAs in patient samples ( n = 43) and for other reasons, such as for not having statistically significant results or wrong miRNA sequence ( n = 6). Finally, the review was performed on a total of 177 studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of those, 166 were excluded for describing HNSCC cases without focus on the larynx ( n = 28), for being exclusively in vitro studies ( n = 39), for having a number of patients less than 10 or for using patient data from public databases ( n = 50), for not quantifying miRNAs in patient samples ( n = 43) and for other reasons, such as for not having statistically significant results or wrong miRNA sequence ( n = 6). Finally, the review was performed on a total of 177 studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 …”
Section: Resultsmentioning
confidence: 99%
“…Some miRNAs were reported by more than one study. The most frequently studied tissue miRNA in our paper list was miR-21-5p, whose role in LSCC was described in 14 different papers [ 26 , 28 , 59 , 67 , 110 , 123 , 129 , 130 , 140 , 145 , 147 , 159 , 174 , 176 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study compared the expression of nine miRNAs in benign, premalignant, and malignant laryngeal lesions and found a statistically significant expression of Hs_miR-21_5p, Hs_miR-218_3p, and Hs_miR-210_3p only in the malignant laryngeal lesions. This result could suggest miRNA's role as a biomarker for laryngeal cancers [75][76][77][78]. In particular, Kinoshita et al explained the role of Hs_miR-218_3p in the regulation of migration and invasion of tumor cells via local adhesion pathways: these data could clarify the mechanism of local recurrence and distant metastasis [79].…”
Section: Micro Ribonucleic Acids (Mirnas)mentioning
confidence: 96%
“…The mortality risk associated with SCC is strongly dependent on invasive and metastatic potential. Tuncturk et al reported a proportional correlation between the upregulation of 9 miRNAs and the increased malignancy of the lesions [ 25 ]. Among these miRNAs, the expression of Hsa-miR-106b-3p was 3.01- and 7.31-fold higher in premalignant and malignant groups, respectively, compared to the benign group.…”
Section: Histopathological Features Of Lsccmentioning
confidence: 99%